2020
DOI: 10.3390/en13225974
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Characteristics of External Walls of Wooden Prefab Cross Laminated Timber

Abstract: A balanced combination of heat flows creates suitable conditions for thermal comfort—a factor contributing to the quality of the internal environment of buildings. The presented analysis of selected thermal-technical parameters is up-to-date and suitable for verifying the parameters of building constructions. The research also applied a methodology for examining the acoustic parameters of structural parts of buildings in laboratory conditions. In this research, selected variant solutions of perimeter walls bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Natural materials have the potential to replace conventional insulating materials because of their good acoustic properties, low price, low weight, availability and last but not least their incomparably lower CO 2 emissions and biodegradability [14,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Natural materials have the potential to replace conventional insulating materials because of their good acoustic properties, low price, low weight, availability and last but not least their incomparably lower CO 2 emissions and biodegradability [14,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…At present, they are still in use, although they are mostly only exhibits in open-air museums. Recently, a return to the construction of wooden buildings using the above-mentioned technology has been observed [1,39,40,70,[78][79][80]. Many authors also focus on analysing the condition of historic buildings [81][82][83], in particular, timber structures [84,85], of cultural heritage.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that wooden structures have superior energy-saving performance to reinforced concrete (RC) structures [14][15][16][17][18]. Based on the analyses performed, it was indicated that wood-based buildings have a favorable energy balance in comparison to traditional buildings based on traditional materials [19]. Recent research concluded that CLT generally provides a significant improvement on energy efficiency, and studies on occupants' comfort in buildings have been examined [20,21].…”
Section: Introductionmentioning
confidence: 99%